Covering Environmental Issues beyond Climate Change in Nigerian Press - Ogadimma Emenyeonu (Lingkar Studi Komunikasi (LISKI), 2017)
This study seeks to address the need for diversity in covering environmental issues given that they are multi-dimensional. Journalists have the responsibility of determining what contents are hyped in the media, by so doing they influence audiencesâ€™ reaction to issues. Thus the agenda setting theory of the media was used as the framework for this study as it helped explain why the press emphasizes certain environmental issues over others. Content analysis was employed to analyze four leading Nigerian newspapers to determine their priorities in covering environmental issues. It was found that despite the much pressing local problems like waste disposal/management, pollution, deforestation, open defecation, poor urban planning, nature conservation, loss of biodiversity, over logging etc, the Nigerian press devotes much attention to climate change/global warming coverage. This seems to be a misplaced priority as Nigeria is said to contribute less than one percent of carbon emission that causes global warming. This study argues that while it is necessary to report climate change, it should not be at the expense of more pressing local issues that the citizens have to contend with in their daily living. There is therefore need to devote ample spaces and time to these local issues otherwise the coverage of environmental issues in Nigeria will be akin to the concept of â€œAfghanistanismâ€ where the local media approach issues from the international perspective while dealing with such issues myopically from the local angle.